MANAGING DIGITAL TRANSFORMATION PROJECTS IN ORGANIZATIONS - Khasanov Odilkhon Kaxxorovich (Ecomind Press, 2026)
This article or research work examines the management of organizational digital transformation projects. Digital transformation projects aim to optimize business processes, products and services, as well as customer interactions using digital technologies. The study analyzes the role of modern technologies such as Artificial Intelligence (AI), Big Data, and Blockchain in project management, their advantages, and the challenges that may arise. It also covers methodologies for strategic project planning, resource management, KPI identification, and performance monitoring. The aim of this work is to develop practical and theoretical skills among students and managers for effective management of digital transformation projects, as well as the ability to identify problems and develop optimal solutions.
Keywords: Digital transformation, Digital business model, Project management, Artificial Intelligence (AI), Big Data, Blockchain, KPI (Key Performance Indicators), Innovation, Platform economy, E-commerce.